2018
DOI: 10.5897/ajpp2017.4727
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surgical antimicrobial prophylaxis use in Ethiopia: Prospective study

Abstract: Appropriate use of surgical antimicrobial prophylaxis can prevent approximately 40 to 60% of surgical site infections. Inappropriate use is associated with emergency of antimicrobial resistance, occurrence of side effects and increased health care cost. We aimed to evaluate surgical antimicrobial prophylaxis use of Hawassa University Referral Hospital against standard guideline Prospective observational study was done on 105 patients who undergone major surgical procedure between March 2 and May 2, 2015. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In our study, the duration of SAP administration was not concordant in 28 (26.8%) of patients. This was consistence with a study conducted at Hawassa University Referral Hospital where the duration of SAP administration is concordant in 18.4% of patients taking antibiotics 22 . However, it was lower than the finding of a study conducted in Palestine where only 31.8% of patients received an antibiotic for an appropriate duration 27 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our study, the duration of SAP administration was not concordant in 28 (26.8%) of patients. This was consistence with a study conducted at Hawassa University Referral Hospital where the duration of SAP administration is concordant in 18.4% of patients taking antibiotics 22 . However, it was lower than the finding of a study conducted in Palestine where only 31.8% of patients received an antibiotic for an appropriate duration 27 .…”
Section: Discussionsupporting
confidence: 75%
“…Similar to our study, studies conducted in different parts of Ethiopia reported that a prolonged duration of surgery (more than an hour) was associated with increased risks of SSI 1 , 15 , 20 , 30 . Another study conducted in Hawassa also revealed that the inappropriate use of poor surgical antimicrobial prophylaxis increases the development of antimicrobial resistance, and SSI 22 .…”
Section: Discussionmentioning
confidence: 99%